THE ROLE OF AUDIOBOOKS IN LANGUAGE LEARNING - Norboyeva Zukhra Alijon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Learning methods are changing dramatically as a result of the rapid advancement of technology. As digital technologies, the internet, and mobile applications have grown in popularity, alternative learning tools such as audiobooks have become more popular. Research has shown that using audio materials can facilitate better language learning outcomes, and this paper examines the role of audiobooks in language acquisition, their historical development, and their impact on contemporary learning approaches. Audiobooks are particularly effective in language learning because they improve pronunciation, vocabulary acquisition, and listening comprehension skills.